Evaluation of crack growth behaviors under Mode I static loading for two-part polyurethane adhesives. (September 2022) - Ogawa, Yuki; Naito, Kimiyoshi; Harada, Keisuke; Oguma, Hiroyuki
Abstract: Structural polyurethane adhesives have been developed in recent years. Thin steel adherends bonded with polyurethane adhesives plastically deform in double cantilever beam tests, an energy release rate is affected by plastic deformation of adherends. This study suggests a loading-unloading test to evaluate crack growth behaviors for two types and two adhesive thicknesses of polyurethane adhesives under Mode I static loading even when plastic deformation occurs in the adherends. A load, in which the crack growth is stopped during test pausing after loading in the loading-unloading test, is defined as an arrest load. The arrest load governs crack arrest and crack regrowth of adhesives, and is not affected by plastic deformation of adherends. Thus, an energy release rate by the arrest load defines as critical separation energy. The critical separation energy for polyurethane adhesives is higher for higher tensile modulus and adhesive strength, and a thicker adhesive. Analytical results based on the triangle cohesive zone model using zero-thickness cohesive elements are agreed with the experimental results. Highlights: Arrest load defined in this study governs crack growth and arrest of adhesives. Critical separation energy is defined as mode I energy release rate by arrest load. Critical separation energy is higher for polyurethane with higher strength. Critical separation energy is higher for thicker adhesive of polyurethane.